2018
DOI: 10.5505/agri.2018.61214
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Effect of Proprioceptive Training on Balance in Patients with Chronic Neck Pain

Abstract: Proprioceptive training should be included in physiotherapy programs to improve balance; it decreases the disability level in patients with CNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…A randomized clinical trial evaluated the impact of balance training on JPS in patients with chronic neck pain, and found that joint repositioning accuracy was improved and pain was reduced in the intervention group, while no effect was observed in the control group [97]. Another randomized control trial revealed that proprioceptive training with a gaze direction recognition exercise combined with conventional physical therapy was more effective than conventional physical therapy for patients with chronic neck pain in improving neck disability and balance [98]. In a doubleblind, randomized controlled trial, Saadat et al [99] demonstrated that sensorimotor training combined with traditional physical therapy exercises could be more effective than traditional exercise alone in improving JPS, endurance, dynamic balance, and walking speed in patients with chronic neck pain (Table 2).…”
Section: Proprioceptive Retrainingmentioning
confidence: 99%
“…A randomized clinical trial evaluated the impact of balance training on JPS in patients with chronic neck pain, and found that joint repositioning accuracy was improved and pain was reduced in the intervention group, while no effect was observed in the control group [97]. Another randomized control trial revealed that proprioceptive training with a gaze direction recognition exercise combined with conventional physical therapy was more effective than conventional physical therapy for patients with chronic neck pain in improving neck disability and balance [98]. In a doubleblind, randomized controlled trial, Saadat et al [99] demonstrated that sensorimotor training combined with traditional physical therapy exercises could be more effective than traditional exercise alone in improving JPS, endurance, dynamic balance, and walking speed in patients with chronic neck pain (Table 2).…”
Section: Proprioceptive Retrainingmentioning
confidence: 99%
“…Exploring the effective treatment of neck pain has long been a challenge. For the importance of the sensorimotor control system, treatments aiming to restore sensorimotor function have been proposed as important managements of neck pain, including balance exercise, joint position and movement sense training, gaze direction recognition exercise, sensory discrimination training, and coordinative exercises (Beinert and Taube, 2013;Kälin et al, 2016;Duray et al, 2018;Saadat et al, 2019). These treatments, in essence, either enhance position/motion sense by repeatedly provoking the proprioceptors or correct motor patterns by increasing the targeted muscle activity (Peng et al, 2021).…”
Section: Interventions Sensorimotor Control System Trainingmentioning
confidence: 99%
“…These treatments, in essence, either enhance position/motion sense by repeatedly provoking the proprioceptors or correct motor patterns by increasing the targeted muscle activity (Peng et al, 2021). Abundant evidence has revealed that the proprioceptive training and motor control exercises could improve the joint reposition accuracy and neck disability, and reduce the pain intensity in patients with neck pain, although treatment methods vary among studies (Beinert and Taube, 2013;Sarig Bahat et al, 2015;Duray et al, 2018;Saadat et al, 2019). In a balance exercise, subjects typically need to keep their head upright when standing by a single leg or on a wobble board with/without visual feedback.…”
Section: Interventions Sensorimotor Control System Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Kwag (2016) and Chung and Jeong (2018) have reported that deep cervical flexor activation exercises alleviated pain and improved CNP function. Gallego Izquierdo et al (2016) and Duray et al (2018) described pain reduction and improved function in patients with CNP after neck proprioception training.…”
Section: Introductionmentioning
confidence: 99%